eHealth interventions for eating disorders - Stadler, Johanna; Bilić, Sally Sophie; Bauer, Stephanie (Adapting evidence-based eating disorder treatments for novel populations and settings, 2021)
Effective treatments for the different forms of eating disorders (EDs) exist; however, not all in need have access to or benefit from them. A major challenge is that many individuals with EDs do not seek professional help or do only many years after illness onset, increasing both the risk of a chronic disease progression and rising health costs. Consequently, it is essential to open up novel ways and settings for broadening access to and application of evidence-based treatment approaches. Recently, the potential of eHealth interventions for the prevention and treatment of EDs has become increasingly apparent. eHealth refers to services focusing on the provision of health information and improving health outcomes using the Internet and related modern technologies. Interventions including eHealth are expected to maximize reach, and to be advantageous in terms of costs, availability, in facilitating access to care, dissemination, and long-term provision. In this chapter, we give an overview of the main areas of application and summarize the current state of research on empirically supported eHealth intervention for EDs in order to draw conclusions for clinical practice and future research.
Gesehen am 25.02.2026